A Scarlet A-Line Skirt, Independent and Critical Visual Practice, and the Brit(ish)line: Representing Women’s Leadership in Education Through Values-Based Cartooning - Mendonça, Penelope (Frontiers in Education, 2021)
Cartooning and graphic facilitation (which involves developing visuals in real time with groups) offer increasingly popular yet highly subjective approaches to public engagement, organisational development, communication, research and research dissemination. Values-Based Cartooning can provide an ethical framework for those undertaking and commissioning this kind of practice, and has been employed by the author as a method for accessing and representing diverse perspectives and experiences for more than two decades. This article is situated within the author’s experience as a practitioner undertaking a range of commissions and partnerships relating to education in the UK. What follows is a critical examination of three contexts where Values-Based Cartooning has been used to represent women’s leadership within education: within research into women’s experiences of working and studying in a higher education institution, within grassroots movements led by teachers and school leaders, and within broader campaigns that have educational value. This involves negotiation of complex social issues while developing visuals, including how to treat gender, race and intersectional identities within word/image combinations. Questions are raised about the purposes of visual practice, the roles and responsibilities of practitioners, conditions of production, audience, and social media. What are the benefits, limitations and risks of Values-Based Cartooning in relation to the visual representation of women’s leadership in education? What is the value of portraying the kind of leadership that exists at different levels, including outside of formal, professional roles, beyond classroom practice and system leadership? And finally, how should visual practitioners respond to conflicting values, risk, failure and nuance in relation to women’s leadership, where there is strong desire and need for positive, strengths-based depictions? The author considers her positionality in relation to the type of work undertaken, and asks whether this kind of visual practice may in fact represent a particular form of leadership that warrants further inquiry. This article will be of interest to educators, researchers, facilitators, artists, cartoonists, campaigners, graphic and visual facilitators, practice-based researchers, and those who commission and evaluate visual methods.